Aperçu socio-économique des inondations au Canada et au Québec - Jarochowska, M. A.; Viau, Robert (Assurances)

(untitled) (HEC Montréal, 1986)
Floods in Canada are a very serious individual and collective risk in certain regions. The authors of this article present the problem as a whole and particularly in certain regions whereat given times, it has been fraught with consequences. They are seeking ways to minimize it, thus avoiding damages suffered in the past and which would most likely recur again, unless we take the appropriate steps to restrain the raging waters. Insurance is not a solution, but merely a palliative.